2010
DOI: 10.1002/jbm.a.32925
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ePTFE in prevascularized collagen leads to peri‐implant vascularization with reduced inflammation

Abstract: During the typical healing response to an implanted biomaterial, vascular-rich granulation tissue forms around the implant and later resolves into a relatively avascular, fibrous capsule. We have previously shown that a microvascular construct (MVC) consisting of isolated microvessel fragments suspended in a collagen I gel forms a persistent microcirculation in lieu of avascular scar when implanted. The current study evaluated the potential for microvascular constructs to maintain a vascularized tissue environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Moreover, the electrospun fibers are not rigid and cells most likely can increase the pore size by physical mechanisms. It is also conceivable that this cell isolation device can be functionalized by covalent localization of proangiogenic factors or enveloped completely in autologous adipose derived microvessels to accelerate the formation of a functional vascular bed prior to injection of cells or islets …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the electrospun fibers are not rigid and cells most likely can increase the pore size by physical mechanisms. It is also conceivable that this cell isolation device can be functionalized by covalent localization of proangiogenic factors or enveloped completely in autologous adipose derived microvessels to accelerate the formation of a functional vascular bed prior to injection of cells or islets …”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that neovasculatures comprised of isolated, intact microvessel segments (arterioles, capillaries, and venules) suspended in collagen type I gels (called a microvascular construct (MVC)) 10 spontaneously undergo sprouting angiogenesis in culture and form functional, hierarchical microvascular networks when implanted 4, 11-13 . In this system, a mature microcirculation forms from neovessels generated via angiogenic sprouting that progress into an immature network and subsequently mature via structural adaptation and network remodeling into a microcirculation 4, 13 .…”
mentioning
confidence: 99%
“…We have previously used these MVCs in a number of applications to prevent the progression of ischemic lesions following myocardial infarction 12 to improve biomaterial biocompatibility 11 , to support islet transplantation 14 , and to generate prevascularized tissue constructs 15, 16 . Furthermore, we have developed an in vitro culture system that supports scale up of the MVCs and MVC engineering 17 .…”
mentioning
confidence: 99%
“…Furthermore, as opposed to in vitro studies that impose exogenous matrices such as collagen, fibronectin or matrigel, the ECM in our chambers is entirely fabricated by native stromal cells and remodeled by endogenous mechanisms. These early events –vessel sprout infiltration and matrix deposition-- can be initiated by the chamber itself 35, 36 , thus accelerating the process of tumor integration. Similar approaches could be used to encourage vascularization in tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%